(untitled) (Academicia Globe: Inderscience Research, 2022)
This article analyzes the philosophical essence of Jalaluddin Rumi’s theory of mystical knowledge and the spiritual factors of human perfection in Jalaluddin Rumi’s philosophical views, and reveals the essence of the ideas of religious tolerance in Mawlana Rumi’s viewsrejecting the religious frenzy, extremism, and political violence of the present time, showing the increasing importance of peaceful living in a tolerant, pluralist mood.